Environment-friendly biodiesel production by transesterification of rapeseed oil: effect of reaction parameters - Kiriliauskaitė, Vita; Bendikienė, Vida; Juodka, Benediktas (Journal of Environmental Engineering and Landscape Management, 2013)
The huge energy demand in the industrialized world and the pollution problems caused due to the worldwide consumption of fossil fuels has made it necessary to develop alternative sources of energy. It is estimated that pure biodiesel provides over 90% reduction in unburned hydrocarbons and 75–90% reduction in aromatic hydrocarbons. This results in almost total reduction in sulphur dioxide (which causes acid rains), 40–60% reduction in soot particles, 80% and 10– 15% reduction in carbon dioxide and carbon monoxide emissions respectively. Reduction of poly-aromatic hydrocarbons is extremely important as many of these hydrocarbons are cancer causing and ozone-forming compounds. Biodiesel does not interfere with the carbon cycle or cause climate change (vegetables from which oils are extracted for biodiesel production remove carbon dioxide from the atmosphere to grow).Due to the global drive towards renewable, non-toxic and environmentally acceptable products the ability of the commercial lipolytic enzyme Lipoprime 50T to catalyze the biotechnologically important process of biodiesel (fatty acid methyl esters) production via rapeseed oil transesterification (methanolysis) was investigated. The optimal reaction conditions were determined using titrimetric and simple and accurate thin-layer chromatography and computer analysis methods that enable to follow the changes of all reaction mixture components simultaneously. The effects of molar ratio of substrates, reaction temperature and time, lipase dosage and water content in different organic medium on the composition of the reaction mixture were analyzed.The hydrolytic activity of lipase directly depends on the reaction solvent and the water content required for high yields of the product increases with increasing the reaction medium hydrophobicity. Under the optimal process conditions identified (n-hexane, 40 °C temperature, 66 mg/ml enzyme, water content of 26%, rapeseed oil to methanol molar ratio of 1:16 and reaction time 24 h) the highest biodiesel conversion yield of around 85% was obtained.First published online: 11 Oct 2012